Business Cycle Accounting: Bulgaria after the introduction of the currency board arrangement (1999-2014) - Aleksandar Vasilev (The European Journal of Comparative Economics, 2017)
This paper focuses on explaining the economic fluctuations in Bulgaria after the introduction of the currency board arrangement in 1997, the period of macroeconomic stability that ensued, the EU accession, and the episode of the recent global financial crisis. This paper follows Chari et al. (2002, 2007) and performs business cycle accounting (BCA) for Bulgaria during the period 1999-2014. As in Cavalcanti (2007), who studies the Portuguese business cycles, most of the volatility in output per capita in Bulgaria over the period is due to variations in the efficiency and labor wedges.